Magnetless electromagnetic contactless interrogation technique for unwired conductive resonators. Issue 11 (1st May 2019) - Baù, M.; Ferrari, M.; Ferrari, V.
Abstract : An electromagnetic contactless interrogation technique to induce and sense mechanical vibrations on miniaturised electrically conductive resonant structures is presented. The structures can be used as passive resonant sensors with proximate contactless readout. No use is made of poling magnets or wired connections to the resonator that is not required to have magnetic properties. An external coil arrangement has one driving and two pickup coils. The driving coil generates a DC magnetic field and two AC magnetic fields at different frequencies: one for excitation and one for probing. Both the AC magnetic fields induce eddy currents on the conductive surface of the resonating structure. The eddy currents at the frequency of the excitation field interact with the DC magnetic field causing alternating forces, which can set the resonating structure into vibration. The eddy currents at the frequency of the probing field generate a magnetic field that is modulated by the vibrations and detected by the pickup coils. A mathematical model of the interrogation principle has been derived and confirmed by numerical solutions. The experimental demonstration is provided by results obtained on an aluminium cantilever resonator.